Management of Social Work in Russia: Levels and Major Problems of Implementation - Johnrid Feridovich Vagabov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The author defines the notion of “social work”, and describes the goals and objectives, the object and the subject of this type of social control. The article reviews in detail the levels of management of social work. Analyzed the problematic aspects arising in the process of interaction of these levels of management in social work in Russia, and discusses their solutions.